Defense gene induction in Camelina sativa upon Alternaria brassicae challenge - SANDHYA RAWAT, SAJAD ALI; ANITA GROVER*, NAYANAKANTHA, N.M. CHAMIL (Indian Phytopathology, 2014)
Rapeseed and mustard are one of the most important oilseed crops of India and the production and productivity of this crop has been greatly hampered by the disease â€œAlternaria blightâ€ caused by the necrotrophic fungal pathogen Alternaria brassicae. A study on defense gene induction was undertaken to explore the signalling mechanisms that underline the defense responses of resistant Camelina sativa to alternaria leaf spot disease. The Expression of four selected defense related genes viz., PR 1, PR 3, PDF1.2 and GST was examined after inoculation of the seedlings of C. sativa with A. brassicae at different time intervals. Transcripts of some or all four defense-related genes accumulated at a greater level upon challenge inoculation with A. brassicae locally as well as systemically. These defense-related genes might play an important role in rendering C. sativa resistant to infection by A. brassicae. Methyl jasmonate or salicylic acid also induced some or all of the above mentioned pathogen responsive defense-related genes to varied levels. Pathogenesis-related (PR) genes such as defensin (PDF1.2), which is often used as a marker gene for jasmonic acid (JA) signalling pathway, and PR1,used as a marker gene for salicylic acid (SA) signalling pathway were also induced in response to SA or JA treatment or vice versa, deviating from the signalling pathway in Arabidopsis. These results suggest the involvement of both JA and SA signaling pathways and their cross-talk in C. sativa conferring resistance to A. brassicae.